Work design and task conflict in interdisciplinary groups. Issue 4 (20th January 2020) - Todorova, Gergana; Brake, Matthew R.W.; Weingart, Laurie R.
Abstract : Purpose: The purpose of this paper is to examine the role of enriched group work design and objective and perceived expertise diversity in interdisciplinary research groups with a focus on two critical group processes: task conflict and idea sharing. Design/methodology/approach: Survey data were collected from 148 researchers and their advisors in 29 research labs at two doctorate-granting universities. The study tested the hypothesized model using hierarchical ordinary least squares regression and hierarchical linear modeling. Findings: Results showed that objective and perceived (salient) expertise diversity jointly influenced task conflict. In addition, whether task conflict had a positive or negative impact on idea sharing depended on group work design enrichment and expertise diversity salience. Idea sharing improved group outcomes over and above the effects of task conflict. Research limitations/implications: Although this study could not test the causal relationships owing to a cross-sectional nature of data, it provides theoretical implications for the group work design, diversity and conflict literature. Practical implications: Group work design represents an important tool for stimulating idea sharing in research groups. The findings suggest that managers should consider and manage the level of expertise diversity salience and the level of task conflict to increase the effectiveness of group work design. Originality/value: The study provides insights on when task conflict may help creative groups. Work design and diversity salience represent important contextual features. The paper also examines both the objective and perceived diversity and disentangles task conflict and idea sharing.